Specific and rapid reverse assaying protocol for detection and antimicrobial susceptibility testing of Pseudomonas aeruginosa based on dual molecular recognition - Yong He (Nature Portfolio, 2021)
Abstract The worldwide emergence and spread of antimicrobial resistance is accelerated by irrational administration and use of empiric antibiotics. A key point to the crisis is a lack of rapid diagnostic protocols for antimicrobial susceptibility testing (AST), which is crucial for a timely and rational antibiotic prescription. Here, a recombinant bacteriophage tail fiber protein (TFP) was functionalized on magnetic particles to specifically capture Pseudomonas aeruginosa, while fluorescein isothiocyanate-labeled-magainin II was utilized as the indicator. For solving the magnetic particles’ blocking effects, a reverse assaying protocol based on TFP recognition was developed to investigate the feasibility of detection and AST of P. aeruginosa. P. aeruginosa can be rapidly, sensitively and specifically detected within 1.5 h with a linear range of 1.0 × 102 to 1.0 × 106 colony forming units (CFU)⋅mL−1 and a detection limit of 3.3 × 10 CFU⋅mL−1. Subsequently, AST results, which were consistent with broth dilution results, can be obtained within 3.5 h. Due to the high specificity of the TFP, AST can actually be conducted without the need for bacterial isolation and identification. Based on the proof-of-principle work, the detection and AST of other pathogens can be extended by expressing the TFPs of their bacteriophages.